ASYMMETRIC-SYNTHESIS OF THE TAXOL AND TAXOTERE C-13 SIDE-CHAINS - Bunnage, M; Davies, S; Goodwin, C (1994)
A practical and efficient asymmetric synthesis of the 3-benzoylamino-2- hydroxy-3-phenylpropionic acid derived side chain of the important anticancer agent taxol is described. The pivotal synthetic transformation relies upon the highly diastereoselective tandem lithium amide conjugate addition-electrophilic hydroxylation of tert-butyl cinnamate 4. The resultant anti β-amino- α-hydroxy acid derivative is readily converted to the anti diastereoisomer of the taxol side chain methyl ester, from which the naturally occurring syn configuration is secured by a simple Mitsunobu inversion sequence via a dihydrooxazole intermediate. Under optimal conditions, this straightforward approach provides the taxol side chain methyl ester (-)-15 (natural enantiomer) in four steps and 60% yield from tert-butyl cinnamate 4. The protocol is applied to the preparation of all four taxol side chain stereoisomers and is extended to allow for the synthesis of the side chain of taxotère, a potent taxol analogue.